2017
DOI: 10.1016/j.scitotenv.2017.04.136
|View full text |Cite
|
Sign up to set email alerts
|

Mapping allergenic pollen vegetation in UK to study environmental exposure and human health

Abstract: Allergenic pollen is produced by the flowers of a number of trees, grasses and weeds found throughout the UK. Exposure to such pollen grains can exacerbate pollen-related asthma and allergenic conditions such as allergic rhinitis (hay fever). Maps showing the location of these allergenic taxa have many applications: they can be used to provide advice on risk assessments; combined with health data to inform research on health impacts such as respiratory hospital admissions; combined with weather data to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 68 publications
2
60
0
Order By: Relevance
“…Prescription rates peaked during the months of high environmental pollen over the last 5 years (April, May, June and July). Highest rates of pollen emissions for a variety of plant taxa including Grass, Dock, Sorrell, Nettle, Plantain and Mugwort are found in June and July . This reflects our finding that the months of June and July have consistently the highest levels of prescribing rates over the last 5 years, as it is likely the incidence of a AR peaks in these months across England.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Prescription rates peaked during the months of high environmental pollen over the last 5 years (April, May, June and July). Highest rates of pollen emissions for a variety of plant taxa including Grass, Dock, Sorrell, Nettle, Plantain and Mugwort are found in June and July . This reflects our finding that the months of June and July have consistently the highest levels of prescribing rates over the last 5 years, as it is likely the incidence of a AR peaks in these months across England.…”
Section: Discussionsupporting
confidence: 74%
“…A recent study investigating vegetation taxa which contribute the highest to allergic pollen emission in the UK has shown results which do not correspond with our findings; there is not a higher density of pollen-producing taxa in the eastern/eastern coastal districts of England. 10 Furthermore, average pollen rates produced by the met office reveal the highest emissions to be in southern and central England, not in eastern districts of England. 11 Therefore, this geographical variation cannot solely be explained by pollen exposure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To address this research gap, studies conducted by the HPRU in Environmental Change and Health have focused on mapping the location of allergenic plant species across the UK [84] and relating pollen and land cover with health outcomes, including asthma exacerbation-related hospital admissions [85]. Results of this latter study showed that daily concentrations of grass pollen were significantly associated with adult hospital admissions for asthma in London, with a 4-5 day lag from increased pollen levels to hospital admissions.…”
Section: Aeroallergens/aerosols Risk: the Case Of Pollenmentioning
confidence: 99%
“…(Vernal grasses). However, it is unknown whether particular grass species contribute more to the prevalence of allergic symptoms and related diseases than others [11]. Whilst some grasses have been identified as more allergenic than others in vitro (triggering higher levels of Immunoglobulin E (IgE) antibody production), there is a high degree of cross-reactivity between grass species [12].…”
Section: Introductionmentioning
confidence: 99%